Integrating Intellectual Capital into Enterprise Valuation: A Framework for the Knowledge Economy - Zheng, Shu (Simen Owen Academic Proceedings Series, 2025)
The accelerating transition toward a knowledge-based economy has shifted enterprise value from tangible assets to intellectual capital, encompassing human expertise, organizational processes, and relational networks. Traditional valuation models, including discounted cash flow and multiples, consistently underrepresent these intangible drivers, resulting in a divergence between reported financials and market assessments. To bridge this gap, this study develops a comprehensive framework that integrates intellectual capital considerations with insights from both knowledge-based and resource-based perspectives on the firm. Methodologically, the research combines a systematic review of recent literature, a comparative evaluation of existing intellectual capital models, and a case-based framework illustrated through analyses of Moderna, Alphabet, and Tencent, representing the biotechnology, artificial intelligence, and digital platform sectors, respectively. The findings reveal that human capital serves as a key driver of innovation, structural capital enhances scalability and organizational resilience, and relational capital strengthens trust and market legitimacy, collectively generating valuation outcomes that exceed the explanatory power of conventional models. The study contributes theoretically by unifying strategic management and financial perspectives, and practically by equipping investors, managers, and policymakers with structured tools to identify and measure the true sources of enterprise value. By embedding intellectual capital into valuation processes, this research redefines how competitiveness and growth potential are assessed in the contemporary knowledge economy.